Teacher Job Stress and Satisfaction in Urban Schools: Disentangling Individual, Classroom, and Organizational Level Influences - Ouellette, Rachel R. (Behav Ther, 2017)
Schools remain among the most frequent providers of children’s mental health services, particularly in low income urban settings. Several decades of research have focused on training teachers to implement evidence-based interventions for minimizing disruptive behavior. Studies consistently demonstrate robust improvements in student behavior and learning; however, the impact on teachers’ work-related stress or satisfaction is not well understood. Six urban, high poverty elementary schools were randomly assigned to a school mental health services model (Links to Learning; L2L) for referred, disruptive students or to services and professional development as usual (SAU). Teachers (n = 71, K-4 general education teachers) in L2L schools participated in professional development and consultation in two universal and two targeted interventions to reduce disruptive behaviors and promote learning. Teachers (n = 65) in SAU schools participated in professional development as usual. Multiple regression models examined teacher reports of individual-level self-efficacy, classroom-level student functioning, and school-level organizational health as predictors of stress and satisfaction. Findings revealed no significant difference between conditions on teacher work-related stress or satisfaction. Organizational health was the strongest predictor of stress and satisfaction. Training on and implementation of evidence-based classroom interventions did not appear to significantly impact teachers’ work-related stress or satisfaction. Instead, findings point to organizational climate and teacher connectedness as potential levers for change, supporting prior work on teacher stress and satisfaction in schools. The significance of targeting organizational factors may be particularly significant in urban school districts.